Integrating health and agriculture to maximize the nutritional impact of orange-fleshed sweetpotato: Results from the Mama SASHA - Low, Jan W. (International Potato Center, 2015)
The Mama SASHA project was implemented in select health facilities across Busia and Bungoma districts of Western Province, Kenya. The project was implemented within the existing USAID/Kenya AIDS, Population and Health Integrated Assistance Program (APHIA Plus). The aim of the project was to provide solid evidence for the effectiveness of the innovative approach to integrate promotion of OFSP and production with public health care services. This flyer is a presentation of results of the project endline survey in Western Kenya.